STENOSIS IN NONCORONARY AREAS AND LIFE QUALITY IN ISCHEMIC HEART DISEASE - A. N. Sumin; M. G. Mos’kin; A. V. Bezdenezhnykh; E. V. Korok; A. V. Shcheglova; O. L. Barbarash (Российский кардиологический журнал, 2015)
Aim. To study the influence of noncoronary atherosclerotic stenosis on life quality (LQ) in patients with IHD.Material and methods. Totally 804 patients studied with IHD, that were selected into 4 groups according to presence of noncoronary stenosis (30% and more). To the group without noncoronary stenosis 472 patients were included. Stenotic subgroups (multifocal — MFA) consisted of: 1 group (n=73) — coronary arteries (CA) + extracranial arteries (BCA) + lower extremities arteries (LE), 2 group (n=154) — CA + BCA, and 3 group (n=105) — CA + LE. LQ was assessed with SF-36 questionnaire, depression level — with the questionnaire “Depression scale”Results. In MFA groups the level of depression was significantly higher than in patients without MFA (p<0,001), the highest values were found in the group with three pools involved. Also in the MFA group’s values of LQ were significantly lower, than in those without MFA by the scales: general health, physical functioning, physical condition and emotional condition. Integral parameters of the LQ were significantly lower in MFA (p=0,0439 for physical component and p=0,0347 for psychological). By the results of monofactor regression analysis, the negative influence on physical component of LQ had MFA, severity of CHF, and smoking, female gender, diabetes. In multifactor analysis the negative influence was confirmed for MFA (p=0,031) and for functional class of CHF  (p<0,001). Negative influence on the psychological component of LQ by monofactor regression analysis had the severity of CHF, decrease of left ventricle ejection fraction, female gender and diabetes mellitus. In monofactor analysis the only independent factor that negatively influenced general psychological health was functional class of CHF (p<0,001).Conclusion. In 41% of patients there are comorbid subclinical lesions of noncoronary arterial pools. Presence of MFA negatively influences physical and psychological components of life quality in IHD. In multifactor analysis, the independent factors related to general physical health were MFA and CHF severity, related to general psycho health only — just the severity of CHF.